To analyze the strategies developed for the protection and animal welfare in canines, by the Local Mayor's Office of Engativá, in the city of Bogotá (2022)
The development of this document aims to describe the program and campaigns for animal protection and welfare, for canines, carried out by the Mayor's Office of Engativá of the city of Bogotá DC, of Colombia, which have been implemented since 2018, in order to make the population aware of the implications of responsible ownership and how these help mitigate public health problems and reduce cases of abandonment of dogs as pets. Due to the above, the regulations that exist regarding the issue of animal protection are identified, which leads to the analysis of the district public policy for animal protection and welfare 2014 - 2038, articulating its action plan, in relation to educating citizens to through education and responsible ownership as one of the primary components to ensure compliance with the factors for protection and animal welfare, with the strategies developed from the local development plans of the town in order to improve the quality of life of dogs which are recognized as beings that feel, that have rights and that are part of the daily life of the human being and thus, be able to live in harmony.